2015
DOI: 10.18293/seke2015-110
|View full text |Cite
|
Sign up to set email alerts
|

Toward using Business Process Intelligence to Support Incident Management Metrics Selection and Service Improvement

Abstract: Abstract-Background: Businesses are increasingly dependent on IT services, and providers need to deliver fast, with high quality and low cost. An incident is an event that can lead to loss or disruption of services. Incident management reinstates normal service operation as quickly as possible and mitigates negative impact to business, ensuring agreed levels of service quality. So, reduce resolution time is usually the most important goal for incidents. Aims We aim to obtain knowledge about process and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Table 1 shows the papers that meet criteria 1 and Table 2 shows the papers that meet criteria 2. It can be observed that some papers (e.g., (Van der Aalst, 2013;Trinkenreich et al, 2015)) were classified into multiple maturity phases. The results show that 44 unique papers are classified to the first phase (detect), 14 unique papers were classified to the second phase (predict) and only 7 unique papers were at phase three (recommend).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the papers that meet criteria 1 and Table 2 shows the papers that meet criteria 2. It can be observed that some papers (e.g., (Van der Aalst, 2013;Trinkenreich et al, 2015)) were classified into multiple maturity phases. The results show that 44 unique papers are classified to the first phase (detect), 14 unique papers were classified to the second phase (predict) and only 7 unique papers were at phase three (recommend).…”
Section: Resultsmentioning
confidence: 99%
“…Only 6 papers are classified into the phase 3. Some of the papers are classified into more than one phases, such as ( Van der Aalst, 2013;Spott et al, 2013;Trinkenreich et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…ii.1. Systematic Mapping to find measures suitable for IT Services measurement initiatives (TRINKENREICH et al, 2015a ii.4. Case Study about using Business Process Intelligence for critical process analysis ; ii.5.…”
Section: The Research Methods Followed To Create Sinismentioning
confidence: 99%
“…Some factors contribute to the difficulty in selecting measures and indicators for IT services, such as: (i) lack of approaches to guide IT services indicators selection, (ii) lack of practical examples involving IT service indicators, and (iii) lack of measurement capabilities in IT supporting tools [JÄNTTI et al, 2010] [LEPMETS et al, 2014]. An available list of indicators can help being a start point for insights during measurement selection [TRINKENREICH et al, 2015a].…”
Section: It Service Quality and Measurementmentioning
confidence: 99%
See 1 more Smart Citation